2020
DOI: 10.2478/macvetrev-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Milkability Evaluation of Jersey Dairy Cows by Lactocorder

Abstract: Since there is not enough data about milkability of the Jersey cows, the aim of this paper is to show basic milkability traits of this cattle breed depending on the parity and milk flow curve types. Cows had average daily production (DMY) of 22.23 kg, milk yield per milking (MYM) of 9.72 kg, and average and maximum milk flow about 1.66 and 2.49 kg/min, respectively. Statistical analysis showed that DMY and MYM of the cows in 4th parity was significantly (p<0.05) higher comparing to cows in 1st and 3th parit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
3
5
1
Order By: Relevance
“…The frequencies of curve types ( Table 2 ) resembled findings on Jersey cows ( 30 ); in this study, about 66% of curves were rectangular and descending. In a field study carried out on 497 Holstein cows ( 31 ), 59.4% of total curves were those with a gradual or continuous decrease phase, similar to the percentage (59.53%) of the present study (type 2, type 3, and type 6).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The frequencies of curve types ( Table 2 ) resembled findings on Jersey cows ( 30 ); in this study, about 66% of curves were rectangular and descending. In a field study carried out on 497 Holstein cows ( 31 ), 59.4% of total curves were those with a gradual or continuous decrease phase, similar to the percentage (59.53%) of the present study (type 2, type 3, and type 6).…”
Section: Discussionsupporting
confidence: 84%
“…Presence of long BT increases management costs and mastitis risk as a result of tissue stress and may indicate suboptimal udder pre-milking stimulation. In other species, it has been demonstrated that the reduction of BT is essential to improve udder health, longevity, and milking efficiency ( 30 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a daily milk yield ranging between 1.70 to 10.20 kg and peak milk flow rate ranging between 0.43 and 4.95 kg/min, these animals showed a great array for selection. Mean peak and average milk flow rates recorded for our dairy camels were lower than those recorded also by Lactocorder ® in dairy Holstein cows [45,46] but range within the values reported in Jersey cows [47]. With higher milk yield/milking (9.72 ± 2.98 kg) and longer milking duration (5.71 ± 2.34 min and 9.94 ± 2.23 min for main milking duration and total milking duration) these authors registered 2.49 ± 0.57 kg/min and 1.66 ± 0.36 kg/min, respectively, for peak and average milk flow rates.…”
Section: Discussionsupporting
confidence: 81%
“…While parity affected significantly milk yield/ milking, peak and average milk flow rates, lactation stage had no effect on the above traits in the studied group. Similarly, significant effect of parity was reported on milkability traits [29] but also a significant effect of lactation stage was reported [47]. Time to milk ejection registered for our dairy camels was less than a minute without udder manual stimulation nor calf presence.…”
Section: Discussionsupporting
confidence: 80%
“…Milk flow curves are affected by parity, DIM, maximum milk flow, and most importantly, by pre-milking operations (Sandrucci et al, 2007). Bobić et al (2020) state that dairy cows with a bimodal milk flow curve had significantly lower average milk flow and longer descending phase of the milk flow curve.…”
Section: Introductionmentioning
confidence: 99%